Prevalence of IgM and IgA Antibodies for the Respiratory Syncytial Virus in Infants and Young Children in Baghdad - M. Naif, Hassan.; M. Ahmad, Zaineb.; G. Al hamadani, Faisal. (Iraqi Journal of Science, 2023)
Respiratory Syncytial Virus is the most common cause of acute viral bronchiolitis and pneumonia in infants and young children. This study is designed to examine the presence of anti-RSV IgM and IgA antibodies in infants and young children aged between 2 months up to 5 years old. ELISA was used to examine the levels of IgM and IgA antibodies in the serum samples from 90 individuals (60 are with respiratory symptoms and 30 healthy as controls). The results were analysed by systematically dividing those individuals into two groups according to their age and clinical status. The age groups included infant between 2 months and 1 year of age and young children between 2-5 years whereas the clinical grouping includes the severity of infection of those hospitalized with acute respiratory symptoms and /or with chest pain from two main children hospitals in Baghdad. ELISA results revealed that anti-RSV IgM levels were 80% and 72% for those with acute infection and those with chest pain, respectively, whereas the levels of IgA were 45% for both groups. On the other hand, the level of IgM for individuals from group I and group II of age distribution were 63% and 35%, respectively; while the levels of IgA were only 27% for group I and 8% for group II. This study showed that the level of IgM antibodies for RSV is indicative of early detection of viral infection and it is more likely to be associated with the onset of recent infection with RSV regardless of the severity of infection. By including another test together with IgM detection may significantly improve early detection of RSV infections. These results may contribute for better understanding for the prevalence of RSV among infants and young children as well as the status of respiratory infection with RSV in children from Baghdad areas which may eventually lead to better rationale for the unnecessary prescription of antibiotics in community.